IMAGES OF POST-COLONIAL THIRD WORLD IN V. S. NAIPAUL - Dhaka, Rajesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Naipaul’s writings are mere end result of colonial and post colonial socio-political discourse. His social, cultural and political portrayals of emerging international locations are about the dependencies of 1/3 world international locations on preferred powers. His observations are very pessimistic, squalid and sever. Although, he writes from west’s affiliation as his critics mark about him, he in a roundabout way makes all jap countries and those aware of the mimicry, rootlessness, nativism, westernization and closing destiny of dependency.